ВИЗНАЧЕННЯ ПАРАМЕТРІВ ТИПОВИХ ЦИФРОВИХ СТАТИЧНИХ РЕГУЛЯТОРІВ ПРОМИСЛОВИХ ЕЛЕКТРОПРИВОДІВ - Шуруб, Ю.В. (Інститут електродинаміки НАН України, Київ, 2023)
The paper is devoted to the development of an analytical method for determining the settings of typical digital static regulators of industrial electric drives, which can be represented as discrete transfer functions in the Z-transform. It is offered to define parameters of adjustment of static regulators, proceeding from the set static error (statism). The possibility of technical realization of the digital proportional-differential regulator with an ideal digital differentiator is substantiated. Significant improvement of system performance indexes when using the differential component of a digital static controller is shown. References 10, figures 7.